Development of A Smart Module on Hydrological Cycle Based on SDGs as A Source of Science Studies for Primary School Students - Santa Santa; Suci Siti Lathifah; Delima Nur Aulia; Azzura Gryniprillady Meyradhia (Jurnal Penelitian Pendidikan IPA, 2024)
The purpose of creating smart modules is to enhance the quality of technology-based learning and increase student-teacher engagement, based on the Sustainable Development Goals (SDGs). This e-module development employs research and development (R&D) methods to produce and evaluate educational products. The aim of product development is to enhance practicality, efficiency, and effectiveness, which are evaluated through testing. The interactive module was validated by electronic media experts, linguists, and material experts, achieving a validation rate of 93.80%, 98.40%, and 94%, respectively. These results indicate that the module is highly effective and valid. According to the Electronic Readability Test, the module scored 97.50%, placing it in the highly suitable category. The effectiveness of the smart module product on water cycle material was evaluated based on the average pretest, posttest, and n-gain scores, as well as teacher and student response questionnaires from 15 respondents. The average pretest, posttest, and n-gain scores were 64.66, 86.33, and 0.60 (60%), respectively, indicating a medium level of effectiveness with a fairly effective outcome. Furthermore, according to teacher and student surveys, 92% and 93.80% respectively found the software to be highly suitable. So, it can be concluded that the a smart module considered valid, practical, and effective.